Perlindungan Hukum Konsumen terhadap Kekurangan Takaran Minyak Goreng Kemasan dalam Perspektif UU Perlindungan Konsumen - Rissal Muhemin; Yulia Rahman; Tiara Na Fasha; Sintong Arion Hutapea (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
This study examines legal protection for consumers regarding discrepancies in packaged cooking oil volume based on Law No. 8 of 1999 on Consumer Protection. The research employs a normative legal method with statutory, conceptual, and case approaches. The findings indicate that businesses reducing product volume without clear notification violate consumer rights and UUPK provisions. Law enforcement mechanisms include government supervision, sanctions, and consumer protection institutions. To enhance consumer protection, stricter monitoring, firm regulations, and public education are necessary.